233 Autoantibody-positive healthy individuals constrain T cell pathways to regulate autoimmune disease. (April 2019) - Slight-Webb, Samantha; Bylinska, Aleksandra; Smith, Miles; Lu, Rufei; Chen, Hua; Bean, Krista; Munroe, Melissa; Maecker, Holden; Utz, Paul J; Merrill, Joan T; Chakravarty, Eliza; Arriens, Cristina; et al.
Abstract : Background: Anti-nuclear antibody (ANA) positivity is a principal feature of individuals with an autoimmune disease, yet up to one in five healthy individuals are ANA-positive (ANA+) and will never develop overt disease. Understanding differences in immune cell physiology between ANA+healthy individuals and individuals with clinical SLE remains a critical goal in the understanding of SLE pathogenesis across ethnicities. Methods: Blood specimens and information on disease activity were collected from European (EA) and African American (AA) individuals classified and matched in groups as ANA- healthy controls (n=24), ANA +healthy (n=24) or SLE patients (n=24). Single-cell analysis of cell surface markers was completed by mass cytometry on PBMCs and cellular heterogeneity was visualized using tSNE (figure 1 A–B) and manual gating. Further, phospho-specific flow cytometry was used to measure basal levels of pERK, pPLCg2 and p38 and expression following CD3/CD28 (TCR) and anti-IgG and IgM (BCR) stimulation. Whole genome RNA-sequencing was performed on flow cytometry sorted T cells, B cells and monocytes from 35 matched ANA-, ANA +and SLE patients followed by weighted correlation network analysis (WGCNA) and pathway enrichment analyses. Results: Both European and African American SLE patients were distinguished from healthy individuals by T cell proliferation (p=0.002) (figure 1 C), plasmacytoid dendritic cell activation (p=0.021) and elevated stem cell factor (p=0.0003). EA ANA+healthy individuals exhibited greater immune regulation with reduced T cell numbers (p=0.002) (figure 1 C), decreased activation of dendritic cells (p=0.039) and transitional B cells (0.033), and elevated expression of the inhibitory receptor CD85j (p=0.042) on specific immune cell subsets compared to ANA- healthy subjects. Further, a module associated with hematopoiesis, T cell activation and intrinsic apoptosis signaling pathways is expressed at a higher level in T cells of EA ANA+individuals. In contrast, AA ANA+healthy individuals had elevated plasma levels of IL-6 (p=0.018) and reduced inhibitory receptor expression (p=0.0089) compared to ANA- healthy controls. Gene expression modules associated with viral responses and type I IFN pathway activation were identified in AA SLE patient B cells, while similar expression modules were only found in the monocytes of European American SLE patients. Conclusions: These results highlight the importance of stem cell factor and T cell expansion in SLE pathogenesis, and suggest that mechanisms of SLE pathogenesis differ by ethnicity. ANA +European Americans may have more effective regulatory mechanisms in place to prevent transition to classified autoimmune disease. Funding Source(s): This work was supported by the NIH under award numbers U54GM104938, U01AI101934, U19AI082714, and P30AR053483.